2020
DOI: 10.21608/ejm.2019.16809.1115
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Aminoglycoside Resistant Acinetobacter baumannii to Antibiotic Combinations

Abstract: A CINETOBACTER baumannii (A. baumannii) is considered one of the predominant antibiotic resistance pathogens involved in hospital acquired infections worldwide problem. The study investigated the effect of antibiotic combination of β-lactams (ceftriaxone, cefixime, carpabenem and impenim) and aminoglycosides against 5 clinical isolates of A. baumannii multidrug resistant. Over one year, 250 bacterial isolates were collected from 5 Egyptian hospitals from various infection sites. Two hundred out of 250 bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…A study in China also found total resistance to cefazolin and 71.8% to cefuroxime ( 34 ). High resistance percentages to cefoperazone (61%), cefixime (99%), and cefuroxime (96%) were also reported from 250 bacterial isolates in Egypt ( 35 ). A high resistance percentage in the cephalosporin class may occur due to A. baumannii having an AmpC cephalosporinase-type enzyme that is chromosomally encoded by all A. baumannii strains ( 36 ).…”
Section: Discussionmentioning
confidence: 93%
“…A study in China also found total resistance to cefazolin and 71.8% to cefuroxime ( 34 ). High resistance percentages to cefoperazone (61%), cefixime (99%), and cefuroxime (96%) were also reported from 250 bacterial isolates in Egypt ( 35 ). A high resistance percentage in the cephalosporin class may occur due to A. baumannii having an AmpC cephalosporinase-type enzyme that is chromosomally encoded by all A. baumannii strains ( 36 ).…”
Section: Discussionmentioning
confidence: 93%
“…MRSA and A. baumannii are the most common pathogens causing HAIs in Egypt [ 41 , 75 ]. Therefore, time–kill curves and TEM images for treated bacteria were performed only for those bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the current study is considered the first assessment of the antibacterial activity and safety of ZnO-NPs compared to a commercial alcohol-based hand sanitizer (Sterillium) that is commonly used in Egyptian hospitals and communities [ 38 ]. In the current study, ZnO-NPs were synthesized chemically, and the antibacterial activity of their colloidal solution in comparison to Sterillium was investigated against multidrug-resistant bacteria that are commonly known to cause HAIs in Egypt: Acinetobacter baumannii (A. baumannii), Klebsiella pneumoniae (K. pneumoniae), Methicillin-resistant Staphylococcus aureus (MRSA), and Staphylococcus aureus (S. aureus) [ 39 , 40 , 41 ]. The cytotoxicity of these formulations to human dermal fibroblast cells was also assessed to ascertain the biosafety (in vitro) of ZnO-NPs to replace alcohol-based hand sanitizers in healthcare settings.…”
Section: Introductionmentioning
confidence: 99%